Hippophae rhamnoides L. (sea buckthorn) mediated green synthesis of copper nanoparticles and their application in anticancer activity - Dadhwal, Pooja; Dhingra, Harish Kumar; Dwivedi, Vinay; Alarifi, Saud; Kalasariya, Haresh; Yadav, Virendra Kumar; Patel, Ashish (Frontiers in Molecular Biosciences, 2023)
Green synthesis of nanoparticles has drawn huge attention in the last decade due to their ecofriendly, biocompatible nature. Phyto-assisted synthesis of metallic nanoparticles is widespread in the field of nanomedicine, especially for antimicrobial and anticancer activity.Here in the present research work, investigators have used the stem extract of the Himalayan plant Hippophae rhamnoides L, for the synthesis of copper nanoparticles (CuNPs). The synthesized of CuNPs were analyzed by using sophisticated instruments i.e. Fourier transform infrared spectroscopy (FTIR), UV-Vis spectroscopy, X-ray diffraction (XRD), highperformance liquid chromatography (HPLC), and scanning electron microscopy (SEM). The size of the synthesized CuNPs was varying from 38 nm to 94 nm which were mainly spherical in shape. Further, the potential of the synthesized CuNPs was evaluated as an anticancer agent on the Hela cell lines, by performing an MTT assay. In the MTT assay, a concentrationdependent activity of CuNPs demonstrated the lower cell viability at 100 µg/mL and IC50 value at 48 µg/mL of HeLa cancer cell lines. In addition to this, apoptosis activity was evaluated by reactive oxygen species (ROS), DAPI (4′,6-diamidino-2-phenylindole) staining, Annexin V, and Propidium iodide (PI) staining, wherein the maximum ROS production was at a dose of 100 µg per mL of CuNPs with a higher intensity of green fluorescence. In both DAPI and PI staining, maximum nuclear condensation was observed with 100 µg/mL of CuNPs against HeLa cell lines.